Slowly but surely - Sarouphim, Ketty (2015)
The purpose of this article is to shed light on the state of gifted education in Lebanon and to describe the efforts underway to establish programs for gifted learners in the country. The article starts with a description of the Lebanese system of education followed by research conducted in Lebanon on an instrument called Discovering Intellectual Strength and Capabilities While Observing Varied Ethnic Responses (DISCOVER), developed at the University of Arizona for the purpose of identifying gifted students from diverse ethnic groups. Next, the results that showed that DISCOVER could be used effectively in Lebanon are presented. Finally, a model for the development of a comprehensive system of education for the gifted nationwide is proposed.